Supramolecular organogel with aggregation-induced emission and liquid crystal properties from 1,3,5-triazine 2,4,6-tricarboxamide for sensing metal ions and colour tunable materials - Umar, Abdulhamid (2019)
The purpose of this research is to develop supramolecular organogel with liquid crystal (LC) mesophase and fluorescent properties for optical application as chemosensor of metal ions and colour tunable materials. The organogel was synthesised utilizing 1,3,5-triazine-2,4,6-tricarboxamide (TZTC12NH) as the self-assembly organic motif. In the first part of the research, TZTC12NH was synthesized in three steps to give a white powder solid in 52% yield. The compound was found to form columnar LC properties with mesophase range of 73.0 to 185.0oC and gave fluorescent emission maxima at 417 and 468 nm upon excitation at 254 nm. The compound was then utilized for the formation of an organogel at 10 wt. % of benzene which gave blue emission upon exposure to a wavelength excitation of 365 nm under a hand-held UV lamp. This organogel showed two emission bands centered at 417 and 468 nm with enhanced intensity when excited at 254 nm. Besides, the organogel shifted the columnar LC mesophase of TZTC12NH to 61.3 - 178.2oC. Polarized optical microscope imaging indicated that the organogel displayed a focal conic fan-like texture for typical arrangements of discotic hexagonal columnar LC. The organogel was utilized as chemosensor of metal ions via fluorescent quenching which showed selective response toward Cu2+ and Ag+ ions over other metal ions under consideration. The sensitivity based on linear Stern-Volmer plot Ksv value is 1.183 × 105 M with LOD 1.104 × 10-6 M for Cu2+ ions and Ksv 1.135 × 105 M with LOD 1.057 × 10-6 M for Ag+ ions, respectively. Upon doping the gel with Eu3+ ions at 0.01 M, the blue emission of the gel turned red under hand-held UV lamp and gave a new sharp emission band centered at 617 nm when excited at 250 nm due to the formation of metallogel. In addition, when few drops of methanoic acid were added to the gel, the red emission of the gel turned back to blue with disappearance of the emission band at 617 nm. Hence, this research showed the successful synthesis of new TZTC12NH as simple supramolecular self-assembly organic scaffold for development of organogel, chemosensor and colour tunable material.